The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2016
DOI: 10.1016/j.jconrel.2016.05.056
|View full text |Cite
|
Sign up to set email alerts
|

Intraperitoneal chemotherapy of ovarian cancer by hydrogel depot of paclitaxel nanocrystals

Abstract: Intraperitoneal (IP) chemotherapy is a promising post-surgical therapy of ovarian cancer, but the full potential is yet to be realized. To facilitate IP chemotherapy of ovarian cancer, we developed an in-situ crosslinkable hydrogel depot containing paclitaxel (PTX) nanocrystals (PNC). PNC suppressed SKOV3 cell proliferation more efficiently than microparticulate PTX precipitates (PPT), and the gel containing PNC (PNC-gel) showed a lower maximum tolerated dose than PPT-containing gel (PPT-gel) in mice, indicati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(23 citation statements)
references
References 41 publications
1
21
0
Order By: Relevance
“…Therefore, these findings do not support the expected synergy between the residence time of the drug and its therapeutic effect. The same research group evaluated the efficacy of PTX nanocrystals and microparticulate PTX precipitates loaded on a similar crosslinkable HA hydrogel for the treatment of mice bearing SKOV-3 ovarian cancer tumors [87]. Contrary to outcomes obtained with the PtNP/gel, the PTX nanocrystals exhibited significant tumor suppression upon single IP administration compared with the commercially available Taxol®.…”
Section: Strategies For Ip Delivery and Sustained Release Of Nanomedimentioning
confidence: 99%
“…Therefore, these findings do not support the expected synergy between the residence time of the drug and its therapeutic effect. The same research group evaluated the efficacy of PTX nanocrystals and microparticulate PTX precipitates loaded on a similar crosslinkable HA hydrogel for the treatment of mice bearing SKOV-3 ovarian cancer tumors [87]. Contrary to outcomes obtained with the PtNP/gel, the PTX nanocrystals exhibited significant tumor suppression upon single IP administration compared with the commercially available Taxol®.…”
Section: Strategies For Ip Delivery and Sustained Release Of Nanomedimentioning
confidence: 99%
“…Intraperitoneal (i.p) chemotherapy in other words the infusion of chemotherapeutic agents directly into the peritoneum is a promising option for ovarian cancer therapy due to spread of the disease to the peritoneal cavity [7,30,31]. Although there are some common drawbacks about i.p administration such as complications related to i.p infusion, including abdominal pain, intolerance to a high level of drug, and discomfort related to the catheter implantation, i.p chemotherapy can be beneficial to maintain an effective local drug concentration for a prolonged period and maximize the locoregional effects on residual tumors [30].…”
Section: Intraperitoneal Chemotherapymentioning
confidence: 99%
“…Although there are some common drawbacks about i.p administration such as complications related to i.p infusion, including abdominal pain, intolerance to a high level of drug, and discomfort related to the catheter implantation, i.p chemotherapy can be beneficial to maintain an effective local drug concentration for a prolonged period and maximize the locoregional effects on residual tumors [30]. Another problem about i.p chemotherapy is rapid clearance of small molecule drugs from peritoneal cavity and necessity of frequent dosing [30]. In order to increase the residence time of the chemotherapeutics in the peritoneal cavity controlled release drug carriers, such as microparticles, hydrogels and bioadhesive nanoparticels [31].…”
Section: Intraperitoneal Chemotherapymentioning
confidence: 99%
See 1 more Smart Citation
“…We have reported that mesoporous silica nanoparticles (MSNs) were able to predominately accumulate in tumors following intraperitoneal (IP) administration in a metastatic ovarian cancer mouse model, likely due to the specific interaction between MSNs and the tumor surface . IP‐injected MSNs are largely retained in the peritoneal cavity with a high probability of interacting with tumor tissues, while intravenously (IV) injected NPs are mostly deposited in the liver and spleen . Taking advantage of this finding, we designed a core/shell structure of MSNs with contrast agents both in the core and in the shell to maximize the contrast ability, and also to retain the silica surface properties for interacting with tumors.…”
Section: Introductionmentioning
confidence: 99%